Duvernoy$1 (Bs Atlas of the Human Brain Stem and Cerebellums High-Field MRI: Surface Anatomy, Internal Structure, Vascularization and 3D Sectional Anatomy - Naidich, Thomas P.; Duvernoy, Henri M.; Delman, Bradley N.; Sorensen, A. Gregory; Kollias, Spyros S.; Haacke, E. Mark.; SpringerLink (Online service) (Vienna : Springer Vienna, 2009)
Advanced MRI requires advanced knowledge of anatomy. This volume correlates thin-section brain anatomy with corresponding clinical 3 T MR images in axial, coronal and sagittal planes to demonstrate the anatomic bases for advanced MR imaging. It specifically correlates advanced neuromelanin imaging, susceptibility-weighted imaging, and diffusion tensor tractography with clinical 3 and 4 T MRI to illustrate the precise nuclear and fiber tract anatomy imaged by these techniques. Each region of the brain stem is then analyzed with 9.4 T MRI to show the anatomy of the medulla, pons, midbrain, and portions of the diencephalonin with an in-plane resolution comparable to myelin- and Nissl-stained light microscopy (40-60 microns). The volume is carefully organized as a teaching text, using concise drawings and beautiful anatomic/MRI images to present the information in sequentially finer detail, so the reader easily assimilates the relationships among the structures shown by high-field MRI.
Methods -- Surface Anatomy of the Brain Stem and Cerebellum -- Internal Architecture of the Brain Stem with Key Axial Section -- Major Functions of the Brain Stem -- Structure and Functions of the Cerebellum -- Structural Organization of the Mesencephalic-Diencephalic Junction -- Vascularization of the Cerebellum and the Brain Stem -- Intrinsic Arterial and Venous Territories of the Brain Stem -- Magnetic Resonance Microscopy AT9.4 Tesla -- Cranial Nerves: Intra-Axial and Cisternal Segments -- Advanced Structural MRI -- Gross Sectional Anatomy and 3T MRI Correlations in Axial, Coronal and Sagittal Planes.
Keywords: Medicine; Neurosciences; Radiology; Neuroradiology; Neurology; Neurosurgery; Psychiatry; Medicine & Public Health; Neuroradiology; Imaging / Radiology; Neurology; Neurosurgery; Psychiatry; Neurosciences; Electronic books